Two-sample Mendelian randomization study reveals no causal relationship between inflammatory bowel disease and urological cancers - Zhang, Haoyang; Hu, Can; Zhang, Zhiyu; Li, Peng; Shen, Gang; Sun, Jiale (Frontiers in Genetics, 2023)
Background: The relationship between inflammatory bowel disease (IBD) and urological cancers has been identified in epidemiological and observational studies, but the causality remains uncertain. We examined whether IBD is causally associated with urological cancers in a Mendelian randomization (MR) study. Methods: The causal relationship between IBD, its main subtypes, and urological cancers was investigated using genome-wide association study (GWAS) data. To obtain more reliable conclusions, all outcomes were divided into training and validation sets. Eligible single-nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) based on MR analysis assumptions. The Inverse variance weighted (IVW) method was applied as the main method along with four other complementary methods. Results: In this two-sample MR study, no genetic evidence for the causal effect of IBD on urological cancers was found in either the training or validation sets using the IVW method. Similarly, we did not observe any significant association between Crohn’s disease (CD) or ulcerative colitis (UC) and urological cancers. The results of the other methods are in accordance with those obtained using the IVW method. Conclusion: In this study, we confirmed that IBD is not a causal genetic risk factor for urological cancer in a European population.